Product Re-Engineering A Tool for Brand Sustainability and Growth in Today’s Global and Competitve Market. (International Journal of Scientific Research and Management (IJSRM), 2023)
Discontinuous innovation though attempt to solve consumers most delicate needs but due to changes in trends and preferences, it becomes something of strategic importance for a brand to be re-engineered to improve quality, functions, features, performance amongst others to achieve compatibility. The study sought to establish whether a product or service that goes through some form of disruption (re-engineering) can enhance the competitive advantage of the firm. Relational and conceptual analysis were employed for the study. The study established that a successful re=engineered brand does not strictly follow the diffusion process proposed for innovation products. It also revealed that perceived risk and the cost of developing marketing strategies including communication and promotion is low since the market is already aware of the brand. The inno-early-vators is a major factor towards the growth and sustainability of the re-engineered brand or product. The study again revealed that the higher rate of adoption of a re-engineered brand owes greatly compatibility and reduction in perceived risk.